School‐based interventions to improve emotional regulation skills in adolescent students: A systematic review. Issue 8 (8th September 2022) - Pedrini, Laura; Meloni, Serena; Lanfredi, Mariangela; Rossi, Roberta
Abstract: Introduction: Emotional regulation (ER) is a core variable involved in the onset and maintenance of mental health disorders; therefore, interventions targeting ER in adolescence represent a promising preventive action. The current systematic review provides a synthesis of the evidence on school‐based interventions on ER in adolescent students. Methods: Six electronic databases (Medline, Psychology Database, Embase, Scopus, Psychinfo, and Web of Science) were searched. The methodological quality of the included studies was assessed by the Methodological Index for Nonrandomized Studies. Results: A total of 36 studies were identified. The interventions were based on different theoretic frameworks and focused on different components of ER. There were universal interventions that addressed the entire class, as well as interventions for a selected population of at‐risk students. Only one‐third of the studies were based on manualized programs. Small to moderate effect sizes were found for mental health and ER skills. Only a few studies assessed risky behaviors, and these studies showed a reduction with moderate to large effect size. Studies conducted on high‐risk populations showed medium‐high effect sizes on ER skills. In contrast, studies conducted on unselected samples of students showed greater variability in the outcome estimates. Acceptability analysis and attendance rates suggested that the interventions were well received by students. The lack of follow‐up assessments and the absence of sample‐size calculation were the most frequent methodological weaknesses. Conclusions: The content of the present review could be useful for professionals involved in the planning of school psychological services. Overall, the findings of the current review support the applicability and beneficial effect of school‐based intervention for adolescents. Moreover, the results clearly point out the utility of a multitiered model to structure coordinated and integrated preventive interventions and to optimize resources.